2015
DOI: 10.1523/jneurosci.2310-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Early-Course Unmedicated Schizophrenia Patients Exhibit Elevated Prefrontal Connectivity Associated with Longitudinal Change

Abstract: Strong evidence implicates prefrontal cortex (PFC) as a major source of functional impairment in severe mental illness such as schizophrenia. Numerous schizophrenia studies report deficits in PFC structure, activation, and functional connectivity in patients with chronic illness, suggesting that deficient PFC functional connectivity occurs in this disorder. However, the PFC functional connectivity patterns during illness onset and its longitudinal progression remain uncharacterized. Emerging evidence suggests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
133
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(149 citation statements)
references
References 99 publications
16
133
0
Order By: Relevance
“…[40][41][42] Moreover, recent functional MRI studies have indicated that functional connectivity in the prefrontal cortex increases with the severity of psychotic symptoms, especially in the early stage of schizophrenia. 43,44 As functional hyperconnectivity may be reflected in regional FA increases, [40][41][42] our findings of both positive and negative associations with positive symptoms in 2 closely linked anatomical structures (AF and SLF) support the idea that psychotic symptoms arise from regional irregularities in white matter rather than deficits per se.…”
Section: Discussionsupporting
confidence: 65%
“…[40][41][42] Moreover, recent functional MRI studies have indicated that functional connectivity in the prefrontal cortex increases with the severity of psychotic symptoms, especially in the early stage of schizophrenia. 43,44 As functional hyperconnectivity may be reflected in regional FA increases, [40][41][42] our findings of both positive and negative associations with positive symptoms in 2 closely linked anatomical structures (AF and SLF) support the idea that psychotic symptoms arise from regional irregularities in white matter rather than deficits per se.…”
Section: Discussionsupporting
confidence: 65%
“…In line with these results, recent resting-state fMRI investigations have shown that symptoms of schizophrenia involve widespread hypo-connectivity between frontal areas and temporal, thalamic, and striatal regions Anticevic et al, 2015;Cocchi et al, 2014; van den Heuvel M a n u s c r i p t Sale et al,30 and Fornito, 2014). This hypoconnectivity has often been associated with an early dysregulation in the function of frontal circuitry (Anticevic et al, 2015). An excitatory tDCS paradigm targeting a highly interconnected hub in the lateral frontal cortex, such as the DLPFC, may provide a means to restore widespread patterns of connectivity associated with frontal areas.…”
Section: Schizophreniasupporting
confidence: 68%
“…Such deficits have been consistently associated with altered lateral prefrontal activity (Tan et al, 2005). In line with these results, recent resting-state fMRI investigations have shown that symptoms of schizophrenia involve widespread hypo-connectivity between frontal areas and temporal, thalamic, and striatal regions Anticevic et al, 2015;Cocchi et al, 2014; van den Heuvel M a n u s c r i p t Sale et al,30 and Fornito, 2014). This hypoconnectivity has often been associated with an early dysregulation in the function of frontal circuitry (Anticevic et al, 2015).…”
Section: Schizophreniamentioning
confidence: 77%
“…In contrast, chronic stress is believed to precipitate glutamatergic dysregulation, leading to increased extracellular glutamate, and excitotoxicity, with subsequent synaptic dysconnectivity and reduced synaptic strength (Bessa et al, 2009;Kang et al, 2012;Yuen et al, 2012). Intriguingly, earlycourse schizophrenia patients were found to have increased PFC GBCr (Anticevic et al, 2015a;Anticevic et al, 2015b). However, following a long course of illness, chronic schizophrenia patients showed significant reduction in PFC GBCr (Anticevic et al, 2015a;Cole et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Details of GBCr methods were previously described (Anticevic et al, 2013;Anticevic et al, 2015a;Anticevic et al, 2014;Anticevic et al, 2015b;Cole et al, 2011;Cole et al, 2012;Driesen et al, 2013a;Driesen et al, 2013b) (see Supplementary Information). GBCr value for each voxel is the average of the correlation between the BOLD time series of a voxel and all other gray matter voxels in the brain.…”
Section: Gbcr Valuesmentioning
confidence: 99%